Neuroimaging Metrics of Drug and Food Processing in Cocaine-Dependence, as a Function of Psychopathic Traits and Substance Use Severity - Denomme, William J.; Simard, Isabelle; Shane, Matthew S. (Frontiers in Human Neuroscience, 2018)
Psychopathic individuals have frequently been characterized as impulsive and irresponsible risk takers, with an altered sensitivity to reward and reward-related stimuli (Beszterczey et al., 2013; Cleckley, 1955; Dean et al., 2013; Hare, 2003; Hopley & Brunelle, 2012; Mitchell et al., 2002; Morgan et al., 2011; Ross et al., 2007; Salim, van der Veen, van Dongen, Franken, 2015; Wallace, Malterer, & Newman, 2009). Given that these are also characteristics that predict initial and prolonged drug use (Koob & Volkow, 2010; Leeman et al., 2014; Woicik et al., 2009), it may come as no surprise that psychopathy has been associated with heightened levels of substance use (Coid et al., 2009; Cope et al., 2012, 2014; Hawes et al., 2015; Hillege et al., 2010; Kennealy et al., 2007), as well as increased diagnosis of both substance abuse (Cauffman et al., 2009; Colins et al., 2015; Jones & Miller, 2012; Mailloux et al., 1997; Sylvers et al., 2011) and substance dependence (Hart et al., 1991; Hopley & Brunelle, 2012; Walsh, et al. 2007). Beyond this behavioral and diagnostic overlap are additional commonalities. For instance, both disorders appear characterized by dysfunction within common corticolimbic regions underlying reward-related processing (psychopathy: Blair, 2015; substance use disorders: Koob & Le Moal, 2001). Within adults with psychopathic traits, this dysfunction appears to manifest as consistently heightened sensitivity to a wide variety of rewarding stimuli within the ventral striatum, including monetary (Bjork et al., 2012; Buckholtz et al., 2010; Carré et al., 2013; Pujara et al., 2013) and drug-related (Buckholtz et al., 2010) rewards (though we note that children/adolescent with heightened callous-unemotional traits often show a normal [Byrd et al., 2018; Murray et al., 2017] or hypsensitive [Veroude et al., 2016] ventral striatal response to reward). Psychopathic traits have also been associated with increased functional connectivity between the ventral striatum and the dorsomedial prefrontal cortex (DMPFC) in response to monetary rewards (Geurts et al., 2016).